The Influence of Mahaprabhu Chaitanyadeb in Contemporary and Post-Chaitanya Society and Literature : A Discussion/ চৈতন্য সমসাময়িক ও চৈতন্যোত্তর সমাজ ও সাহিত্যে মহাপ্রভু চৈতন্যদেবের প্রভাব : একটি আলোচনা (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
In the evolution of history, Mahaprabhu Shri Chaitanyadeb was a unique character, the ruler of time, and the lord of the era during the Middle Ages. His advent was a revolutionary event in Bengali literature. Mahaprabhu Chaitanyadeb spent 22 years in household life and became a sannyasi at the age of 24. His entire life was full of intense emotions. Centering his life consciousness, the social culture, religious practices of Bengalis—in a word, the entire process of creation and heartfelt love —was shaped. From the sixteenth to the eighteenth century, even in the modern scientific age, his life, character, and practice have created a profound and far-reaching interest in Bengali and beyond, so he can be called a man of the era. The entire society was awakened to a new life in the touch of Shri Chaitanyadeb’s life and words. Just as the greens become vibrant when it rains on barren land.Before his advent, Bengali literature was fragmented and limited due to various complex religious doctrines. The small doctrines transformed into a vast ocean in the tide of the intense emotions suggested by Shri Chaitanya deb. Chaitanya deb brought about a revolutionary change in Bengali social life based on emotion. This wave of emotion spread throughout the social psyche in a short time. Man got a place above the scriptures. The person who first took society outside the home, who had registered the name in the group of Baul outside the house, was Chaitanya deb himself. The immense emotion that was created in society due to his influence became unified in the form of Hindus and Muslims and was tied in one thread. As a result of the advent of Chaitanya deb, there was a renaissance in Bengal. A cultural circle was formed in Bangladesh centering on Chaitanya deb. Generally, it is known as Chaitanya culture or Chaitanya Renaissance. In Bengali poetry, literature, art, sculpture—in all areas of national culture—the pure flame of Chaitanyadeb’s life spread. Now the creative dance of that holy flame began. As a result of Chaitanyadeb’s advent, there were various influences in society, culture, music, philosophy, and literature in contemporary and post-Chaitanya Middle Ages. The society and culture underwent changes, new inventions in music and drama, and originality in the field of literary creation. We will discuss the extensive side of the main subject in our main article.
Keywords: Chaitanyadeb; Bengali Literature; Influence; Philosophy; Baishnab